MANAJEMEN KESEHATAN SAPI PEJANTAN DI BALAI INSEMINASI BUATAN UNGARAN08 - , ANDHIKA BAYU SIS SWA BHUWANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Field practice (PKL) at Balai Inseminasi Buatan Ungaran is carried out to fulfill the obligation of the field practices of the Department of Animal Health (DIII). It is simultaneously in order to collect data for the Final Project (TA). The purpose of this final project is to determine the health management of bull in Balai Inseminasi Buatan Ungaran. The data collection was conducted by directly interviewing the officers, library study, and direct observation along the practices from March 10th to 14th, 2014. The bullâs health management implementation includes cattle bathing, nail care, eradication of ectoparasites, vitamins distributions, prepuce hair cutting, deworming, weighing, sick animals handling in general, handling bull technique, and studâs exercise. The disease preventions including vaccination, laboratory medical examination, and pacification measurement handling. Livestock housing management includes cages care and sanitation.